Preparation method of oxidized nanocellulose doped polyvinyl alcohol-based magnetic functional film
By doping oxidized nanocellulose and magnetic nanoferrous oxide in the polyvinyl alcohol film and loading natural antioxidants, the problems of low strength and poor oxidation resistance of traditional polyvinyl alcohol film are solved, and high mechanical strength and oxidation resistance are achieved. The improvement is suitable for flexible electronics and biomedical fields.
Patent Information
- Application Number
- CN202411598603.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-01-17
AI Technical Summary
The traditional polyvinyl alcohol film has low strength, poor oxidation resistance and poor conductivity, which limits its application in flexible electronic equipment and biomedical fields.
Using the preparation method of polyvinyl alcohol-based magnetic functional film doped with oxidized nanocellulose, the magnetic nano-ferrous oxide is combined with oxidized nanocellulose and loaded with natural antioxidants to form a high mechanical strength, anti-ultraviolet and anti-oxidation function. Membrane material.
It improves the mechanical strength and antioxidant properties of the membrane, enhances the loading effect on natural pigments, simplifies the process flow, reduces energy consumption, and is suitable for flexible electronics and biomedicine fields.
Smart Images

Figure CN119320512A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of preparation of adsorption materials, and in particular to a preparation method of a polyvinyl alcohol-based magnetic functional film doped with oxidized nanocellulose and application thereof. Background Art
[0002] Traditional plastic-based electronic devices are not stretchable, have poor elasticity, and poor biocompatibility. With the rapid development of flexible electronic devices, there is an increasing demand for biocompatible, stretchable, memory-functional, and repairable gel film materials in the fields of electronic skin and flexible electronic devices. Polymer-based skin-friendly wearable flexible materials have received increasing attention due to their ease of manufacturing and cost-effectiveness. Polyvinyl alcohol (PVA) is a biocompatible polymer with low cost, high hydrophilicity, good chemical stability, and good mechanical resistance. PVA gel has the characteristics of water absorption, water retention, sustained release, and sensitivity to external stimuli, as well as low toxicity, good physical and mechanical properties, and excellent biocompatibility. It is widely used in drug sustained release carriers, artificial cartilage organ tissues, biomedicine, sensors, artificial muscles of robotic equipment, chemical storage, optical gates, molecular separation systems, and other fields. Magnetic nano-iron oxide has a large number of hydroxyl groups on its surface. Its synthesis method is simple and easy to combine with other components. It has excellent reactivity, unique adsorption properties, ion exchange capacity, low cost, and catalytic properties, and has attracted much attention, showing potential application prospects in various fields. However, bare magnetic nanoparticles are prone to aggregation and have poor acid stability, which limits their application. In order to increase their interaction with other nanoparticles and polymer matrices, magnetic nanoparticles were coated, oxidized nanocellulose was added as a dopant and coupling agent, magnetic PVA polyvinyl alcohol-based nanocellulose composites were constructed, and natural antioxidants were loaded, thus providing a new way to prepare conductive stretchable functional gel membrane materials. Summary of the invention
[0003] In order to overcome the shortcomings and limitations of existing polyvinyl alcohol films such as low strength and poor oxidation resistance, the present invention proposes a method for preparing an oxidized nanocellulose-doped polyvinyl alcohol-based magnetic functional film.
[0004] To achieve the above object, the present invention is achieved through the following technical solutions:
[0005] A method for preparing an oxidized nanocellulose-doped polyvinyl alcohol-based magnetic functional film, characterized in that the preparation method comprises the following steps:
[0006] (1) Preparation of oxidized nanocellulose.
[0007] (2) Preparation of magnetic nano-iron oxide solution: Take a certain amount of ferric chloride and add it to ethylene glycol. Stir it on a magnetic stirrer at room temperature until the ferric chloride is completely dissolved and the solution becomes yellow and transparent. Then weigh sodium acetate and add it to the ferric chloride solution while stirring. Stir for about 2 hours until the solution becomes a thick and uniform brown-yellow color, thereby obtaining a magnetic nano-iron oxide solution.
[0008] (3) slowly adding the obtained magnetic nano iron oxide solution to a certain concentration of pure polyvinyl alcohol solution, stirring with a magnetic force to form a red sol. Then adding a certain amount of oxidized nanocellulose, stirring with a magnetic force for a certain period of time, standing, defoaming, casting into a film, freeze drying, treating with a certain concentration of sodium hydroxide for half an hour, washing with water, and drying to obtain a magnetic polyvinyl alcohol functional film doped with oxidized nanocellulose.
[0009] (4) Polyvinyl alcohol-based magnetic functional film loaded with natural antioxidants: The prepared magnetic functional film is immersed in a natural pigment solution with antioxidant function at a certain concentration, treated for a certain period of time, washed with water and dried to obtain a magnetic polyvinyl alcohol functional film with anti-ultraviolet and anti-oxidation functions.
[0010] The method for preparing oxidized nanocellulose in step (1) of the present invention is characterized in that sodium periodate and cellulose are mixed in a molar ratio of 1:0.5-2, placed in a constant temperature oscillating dyeing machine at 30°C-90°C to avoid light for reaction for 1-3 hours, 30-60 mL of 0.1 mol / L ethylene glycol is added to continue the reaction for 0.5 hours, the suspension is taken out, filtered with a circulating water vacuum pump, the filtrate is taken out, 50 mL-150 mL of acetone is added to the filtrate, precipitated in the dark for 2 hours, and the oxidized nanocellulose is obtained after filtration. The particle size of the oxidized nanocellulose is 1-100 nm.
[0011] The cellulosic substances used in the step (1) of preparing oxidized nanocellulose in the present invention are chitosan, cellulose, sodium alginate and starch.
[0012] The preparation method of the magnetic nano-iron oxide solution in step (2) of the present invention is characterized by weighing 2.7 g to 5 g of ferric chloride, adding it to 20 mL to 100 mL of ethylene glycol, stirring it on a magnetic stirrer at room temperature until the ferric chloride is completely dissolved and the solution is yellow and transparent, then weighing 2 g to 10 g of sodium acetate, adding it to the ferric chloride solution while stirring, stirring for about 2 hours, until the solution becomes thick and uniform brown-yellow, and obtaining the magnetic nano-iron oxide solution.
[0013] The preparation of the magnetic nano-iron oxide polyvinyl alcohol solution in step (3) of the present invention is characterized by slowly dropping 50 mL to 100 mL of the magnetic iron oxide solution into 100 mL of a 2% to 10% polyvinyl alcohol solution to form a red sol. The alcoholysis degree of the polyvinyl alcohol used is 85 to 90%.
[0014] As step (3) of the present invention, the magnetic nano iron oxide solution is added to the polyvinyl alcohol solution, characterized in that 50mL to 100mL of the magnetic iron oxide solution is slowly added dropwise to 100mL of 2% to 10% polyvinyl alcohol solution, and stirred magnetically to form a red sol. The alcoholysis degree of the polyvinyl alcohol used is 85 to 90%.
[0015] The preparation of the oxidized nanocellulose-doped magnetic polyvinyl alcohol functional film in step (3) of the present invention is characterized by adding 0.1 g to 1 g of oxidized nanocellulose to the magnetic polyvinyl alcohol solution, magnetically stirring for 2 h to 4 h, standing, defoaming, casting into a film, and freeze-drying.
[0016] As step (3) of the present invention, a method for preparing a polyvinyl alcohol-based magnetic functional film doped with oxidized nanocellulose is characterized in that the prepared film is treated with 0.1 mol / L sodium hydroxide for 0.5h to 1 hour, washed with water, and dried to obtain the oxidized nanocellulose-doped magnetic polyvinyl alcohol functional film.
[0017] The step (4) of the present invention is characterized in that the prepared magnetic polyvinyl alcohol functional film can be used to load natural pigments with antioxidant function. The concentration of natural pigments is 1g / L to 8g / L, wherein the natural pigments include curcumin, rose bengal, luteolin and other natural pigment substances with antioxidant function.
[0018] In step (4) of the present invention, the characteristics include that the magnetic polyvinyl alcohol film doped with nanocellulose loaded with natural pigments has anti-ultraviolet and anti-oxidation functions and high mechanical strength.
[0019] Compared with the prior art, the present invention has the following advantages:
[0020] (1) The cross-linking agent used in the present invention is oxidized nanocellulose containing aldehyde groups, hydroxyl groups, etc., which enhances the cross-linking between polyvinyl alcohols and can serve as a reducing agent to promote the reduction and fixation of nano-iron oxide.
[0021] (2) The present invention overcomes the defects of the traditional polyethanol membrane, such as low strength, poor antioxidant function and poor electrical conductivity.
[0022] (3) The prepared magnetic functional membrane has a good loading effect on natural pigments. During the adsorption process, there is no need to adjust the pH of the pigment solution or add additives, and a high adsorption rate can be achieved, thereby reducing energy consumption.
[0023] (4) The method described in the present invention is environmentally friendly, energy-saving, simple in process, easy to operate, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The surface morphology of the prepared oxidized cellulose-doped magnetic functional film;
[0025] Figure 2 Loading natural pigments on oxidized nanocellulose-doped magnetic polyvinyl alcohol functional membranes. DETAILED DESCRIPTION
[0026] Embodiment 1:
[0027] 2.7g of ferric chloride was added to 80mL of ethylene glycol, and stirred on a magnetic stirrer at room temperature until the ferric chloride was completely dissolved and the solution was yellow and transparent. Then 2g of sodium acetate was weighed and added to the ferric chloride solution while stirring for about 2h until the solution became thick and uniform brown-yellow to obtain a magnetic nano-iron oxide solution. Then 50mL of magnetic nano-iron oxide solution was mixed with 100mL of 5% polyvinyl alcohol solution, stirred for 1h, 0.5g of oxidized nano-cellulose was added, stirred for 2h, allowed to stand, defoamed, cast into a film, freeze-dried at -45℃ for 48h, treated with 0.1mol / L sodium hydroxide for 0.5h, washed with water, and dried to obtain a magnetic polyvinyl alcohol functional film doped with oxidized nano-cellulose.
[0028] Embodiment 2:
[0029] 2.7g of ferric chloride was added to 80mL of ethylene glycol, and stirred on a magnetic stirrer at room temperature until the ferric chloride was completely dissolved and the solution was yellow and transparent. Then 2g of sodium acetate was weighed and added to the ferric chloride solution while stirring for about 2h until the solution became thick and uniform brown-yellow to obtain a magnetic nano-iron oxide solution. Then 50mL of magnetic nano-iron oxide liquid was mixed with 100mL of 5% polyvinyl alcohol solution, stirred for 1h, 0.5g of oxidized nanocellulose was added, stirred for 2h, allowed to stand, defoamed, cast into a film, freeze-dried at -45℃ for 48h, treated with 0.1mol / L sodium hydroxide for 0.5h, washed with water, and dried to obtain a magnetic polyvinyl alcohol functional film doped with oxidized nanocellulose. The obtained oxidized nanocellulose doped magnetic polyvinyl alcohol functional films were immersed in curcumin with a concentration of 0.5g / L for 1h, then washed with water, and dried to obtain the corresponding curcumin-loaded functional films.
[0030] Embodiment 3:
[0031] 2.7g of ferric chloride was added to 80mL of ethylene glycol, and stirred on a magnetic stirrer at room temperature until the ferric chloride was completely dissolved and the solution was yellow and transparent. Then 2g of sodium acetate was weighed and added to the ferric chloride solution while stirring for about 2h until the solution became thick and uniform brown-yellow to obtain a magnetic nano-iron oxide solution. Then 50mL of magnetic nano-iron oxide liquid was mixed with 100mL of 5% polyvinyl alcohol solution, stirred for 1h, 0.5g of oxidized nanocellulose was added, stirred for 2h, allowed to stand, defoamed, cast into a film, freeze-dried at -45℃ for 48h, treated with 0.1mol / L sodium hydroxide for 0.5h, washed with water, and dried to obtain a magnetic polyvinyl alcohol functional film doped with oxidized nanocellulose. The obtained oxidized nanocellulose doped magnetic polyvinyl alcohol functional film was immersed in rose bengal at a concentration of 0.5g / L for 1h, then washed with water, and dried to obtain the corresponding curcumin-loaded functional film.
[0032] Embodiment 4:
[0033] 2.7g of ferric chloride was added to 80mL of ethylene glycol, and stirred on a magnetic stirrer at room temperature until the ferric chloride was completely dissolved and the solution was yellow and transparent. Then 2g of sodium acetate was weighed and added to the ferric chloride solution while stirring for about 2h until the solution became thick and uniform brown-yellow to obtain a magnetic nano-iron oxide solution. Then 50mL of magnetic nano-iron oxide solution was mixed with 100mL of 5% polyvinyl alcohol solution, stirred for 1h, 0.5g of oxidized nanocellulose was added, stirred for 2h, allowed to stand, defoamed, cast into a film, freeze-dried at -45℃ for 48h, treated with 0.1mol / L sodium hydroxide for 0.5h, washed with water, and dried to obtain a magnetic polyvinyl alcohol functional film doped with oxidized nanocellulose. The obtained oxidized nanocellulose-doped magnetic polyvinyl alcohol functional film was immersed in 0.5g / L luteolin for 1h, then washed with water and dried to obtain the corresponding curcumin-loaded functional film.
[0034] Embodiment 5:
[0035] 2.7g of ferric chloride was added to 80mL of ethylene glycol, and stirred on a magnetic stirrer at room temperature until the ferric chloride was completely dissolved and the solution was yellow and transparent. Then 2g of sodium acetate was weighed and added to the ferric chloride solution while stirring for about 2h until the solution became thick and uniform brown-yellow to obtain a magnetic nano-iron oxide solution. Then 50mL of magnetic nano-iron oxide solution was mixed with 100mL of 5% polyvinyl alcohol solution, stirred for 1h, 1g of oxidized nanocellulose was added, stirred for 2h, allowed to stand, defoamed, cast into a film, freeze-dried at -45℃ for 48h, treated with 0.1mol / L sodium hydroxide for 0.5h, washed with water, and dried to obtain a magnetic polyvinyl alcohol functional film doped with oxidized nanocellulose. The obtained magnetic polyvinyl alcohol functional film doped with oxidized nanocellulose was immersed in luteolin with a concentration of 0.5g / L for 1h, then washed with water and dried to obtain the corresponding curcumin-loaded functional film.
[0036] Embodiment 6:
[0037] 2.7g of ferric chloride was added to 80mL of ethylene glycol, and stirred on a magnetic stirrer at room temperature until the ferric chloride was completely dissolved and the solution was yellow and transparent. Then 2g of sodium acetate was weighed and added to the ferric chloride solution while stirring for about 2h until the solution became thick and uniform brown-yellow to obtain a magnetic nano-iron oxide solution. Then 50mL of magnetic nano-iron oxide solution was mixed with 100mL of 5% polyvinyl alcohol solution, stirred for 1h, 2g of oxidized nanocellulose was added, stirred for 2h, allowed to stand, defoamed, cast into a film, freeze-dried at -45℃ for 48h, treated with 0.1mol / L sodium hydroxide for 0.5h, washed with water, and dried to obtain a magnetic polyvinyl alcohol functional film doped with oxidized nanocellulose. The obtained oxidized nanocellulose-doped magnetic polyvinyl alcohol functional film was immersed in luteolin with a concentration of 0.5g / L for 1h, then washed with water and dried to obtain the corresponding curcumin-loaded functional film.
[0038] Table 1 UPF value and antioxidant activity of functional membrane loaded with natural pigments
[0039]
[0040] As can be seen from Table 1, the surface color depth, anti-ultraviolet performance and antioxidant activity of the functional membranes are different with different loaded pigments. Using the same pigment luteolin, as the amount of oxidized nanocellulose increases, the apparent color depth K / S of the functional membrane increases, and the anti-ultraviolet performance, antioxidant activity and strength of the functional membrane after loading luteolin are enhanced.
[0041] Surface color depth value K / S: Use Color-Eye7000A computer color matching system to test K / S value.
[0042] Anti-ultraviolet performance: The YG(B)912E textile anti-ultraviolet performance tester was used to test the UPF index of the film in the ultraviolet range of 200-700nm. Each sample was repeated 3 times in different areas, and then the average value was calculated.
[0043] Mechanical strength test: The physical and mechanical properties of the gel film were tested using a micro-controlled electronic universal testing machine model CMT4304.
[0044] Antioxidant activity determination: Cut the membrane into 1cm*1cm pieces, cut them into pieces and react them with 25ml of anhydrous ethanol for more than 12h. Take samples into test tubes according to the gradient, such as 100μL, 200μL, 300μL, 400μL, 500μL, and then add anhydrous ethanol to 3mL of the sample and add 1mL DPPH. After treating in the dark for 30min, measure its absorbance at 517nm. The calculation formula for antioxidant activity is:
[0045]
[0046] Where: As is the absorbance of the sample DPPH solution measured at 517 nm, Ac is the absorbance of anhydrous ethanol at 517 nm, and Ao is the absorbance of pure DPPH at 517 nm.
[0047] The purpose of the present invention is to provide a modification method for wool fabric dyeing with acid dyes, which can achieve low-temperature dyeing effect without adjusting pH value and adding accelerator. The modification method is environmentally friendly, simple, effective, can reduce energy consumption, and save dyes and chemicals.
[0048] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a polyvinyl alcohol-based magnetic functional film doped with oxidized nanocellulose, characterized in that: The preparation method comprises the following steps: (1) Preparation of oxidized nanocellulose. (2) Preparation of magnetic nano-iron oxide solution: Take a certain amount of ferric chloride and add it to ethylene glycol. Stir it on a magnetic stirrer at room temperature until the ferric chloride is completely dissolved and the solution becomes yellow and transparent. Then weigh sodium acetate and add it to the ferric chloride solution while stirring. Stir for about 2 hours until the solution becomes a thick and uniform brown-yellow color, thereby obtaining a magnetic nano-iron oxide solution. (3) Preparation of magnetic polyvinyl alcohol functional film doped with oxidized nanocellulose: The obtained magnetic nano iron oxide solution is slowly added to a certain concentration of pure polyvinyl alcohol solution, and magnetic stirring is performed to form a red sol. Then a certain amount of oxidized nanocellulose is added, magnetic stirring is performed for a certain period of time, the solution is allowed to stand, defoamed, cast into a film, freeze-dried, treated with a certain concentration of sodium hydroxide for half an hour, washed with water, and dried to obtain a magnetic polyvinyl alcohol functional film doped with oxidized nanocellulose. (4) Polyvinyl alcohol-based magnetic functional film loaded with natural antioxidants: The prepared magnetic functional film is immersed in a natural pigment solution with antioxidant function at a certain concentration, treated for a certain period of time, washed with water and dried to obtain a magnetic polyvinyl alcohol functional film with anti-ultraviolet and anti-oxidation functions.
2. A method for preparing a polyvinyl alcohol-based magnetic functional film doped with oxidized nanocellulose as claimed in claim 1, characterized in that: the preparation of oxidized nanocellulose comprises mixing sodium periodate and cellulose-based substances in a molar ratio of 1:0.5-2, placing in a constant temperature oscillating dyeing machine at 30°C-90°C to react in the dark for 1-3 hours, adding 30-60 mL of 0.1 mol / L ethylene glycol to continue the reaction for 0.5 hours, taking out the suspension, filtering with a circulating water vacuum pump, taking out the filtrate, adding 50 mL-150 mL of acetone to the filtrate, precipitating in the dark for 2 hours, and filtering to obtain the oxidized nanocellulose. The particle size of the oxidized nanocellulose is 1-100 nm. .
3. The oxidized nanocellulose-doped polyvinyl alcohol-based magnetic functional film according to claim 2, characterized in that: The cellulose-based substances include chitosan, cellulose, sodium alginate and starch.
4. The method for preparing a polyvinyl alcohol-based magnetic functional film doped with oxidized nanocellulose according to claim 1, characterized in that: The magnetic nano-iron oxide solution is prepared by weighing 2.7 g to 5 g of ferric chloride, adding it to 20 mL to 100 mL of ethylene glycol, stirring it on a magnetic stirrer at room temperature until the ferric chloride is completely dissolved and the solution is yellow and transparent, then weighing 2 g to 10 g of sodium acetate, adding it to the ferric chloride solution while stirring, stirring for about 2 hours, until the solution becomes thick and uniform brown-yellow, and obtaining a magnetic nano-iron oxide liquid.
5. The method for preparing a polyvinyl alcohol-based magnetic functional film doped with oxidized nanocellulose according to claim 1 is characterized in that: The magnetic nano-iron oxide solution is added to the polyvinyl alcohol solution, wherein 50 mL to 100 mL of the magnetic nano-iron oxide solution is slowly dripped into 100 mL of 2% to 10% polyvinyl alcohol solution to form a red sol. The alcoholysis degree of the polyvinyl alcohol used is 85 to 90%.
6. The method for preparing a polyvinyl alcohol-based magnetic functional film doped with oxidized nanocellulose as claimed in claim 1 is characterized in that The method comprises adding 0.1 g to 1 g of oxidized nanocellulose into a magnetic polyvinyl alcohol solution, stirring for 2 to 4 hours, standing, defoaming, casting into a film, and freeze-drying.
7. The method for preparing a polyvinyl alcohol-based magnetic functional film doped with oxidized nanocellulose as described in claim 1 is characterized in that the prepared film is treated with 0.1 mol / L sodium hydroxide for 0.5 h to 1 h, washed with water, and dried to obtain the oxidized nanocellulose-doped magnetic polyvinyl alcohol functional film.
8. A method for preparing a polyvinyl alcohol-based magnetic functional film doped with oxidized nanocellulose as claimed in any one of claims 1 to 8, wherein the prepared magnetic polyvinyl alcohol functional film can be used to load natural pigments with antioxidant function. The concentration of natural pigments is 1g / L to 8g / L. The natural pigments include curcumin, rose bengal, luteolin and other natural pigment substances with antioxidant function.
9. A method for preparing an oxidized nanocellulose-doped polyvinyl alcohol-based magnetic functional film as described in any one of claims 1 to 9, characterized in that the magnetic polyvinyl alcohol film doped with nanocellulose loaded with natural pigments has anti-ultraviolet and anti-oxidation functions and high mechanical strength.